Cadmium excretion via leaf hydathodes in tall fescue and its phytoremediation potential. (September 2019) - Dong, Qin; Fei, Ling; Wang, Cheng; Hu, Shuai; Wang, Zhaolong
Abstract: Cadmium (Cd) contamination of the soil is one of the most serious environmental problems of agricultural production. Phytoremediation has attracted increasing attention because it can safely remove the soil contaminates via plant uptake, accumulations and plant harvesting. However, the high Cd toxicity to plant tissues and treatment of the large amount of hazardous plant residues from phytoremediation have limited its commercial implementation. Here we show that the leaves of the tall fescue ( Festuca arundinacea ) can excrete Cd out to avoid Cd toxicity in plant tissues. Cd specific fluorescence spectroscopy with laser confocal scanning microscope, screening electron microscope with energy dispersive spectroscopy and guttation fluids analysis confirmed that leaf hydathodes were the pathway of Cd excretion in tall fescue. Element analysis showed that Cd was preferentially excreted out when compared to the ion nutrients. The amount of leaf Cd excretion was linearly increased in response to the Cd stress period. The phytoremediation efficiency was evaluated to remove 14.4% of soil Cd annually by the leaf Cd excretion in our experimental system. These findings indicate that a novel strategy of Cd phytoexcretion based on washing-off and collection of leaf surface Cd is feasible to avoid Cd toxic in plant tissues and the high treatment cost of hazardous plant residues. Graphical abstract: Image 1055 Highlights: Tall fescue leaves can excrete Cd out via hydathodes. Cd is preferentially excreted out onto the leaf surface to avoid its toxicity to plant tissues. The capacity of Cd excretion is satisfactory for a novel strategy of phytoexcretion. Abstract : Main finding: We found that Cd can be excreted out onto the leaf surface via hydathodes to avoid Cd toxicity in tall fescue. The capacity of Cd excretion is satisfactory to develop a novel strategy of Cd phytoexcretion by continuously pumping out Cd from the contaminated soils without plant harvesting.